Tijding en Tendens - Bru, Sascha; Masschelein, Anneleen (Academia Press, 2021)
The central theme of this issue is the singularity of general and comparative literary theory in the Low Countries. How do they combine insights from neighboring linguistic areas, more specifically the dominant French, English and German traditions? In what branches were and are Flemish and Dutch literary theorists specifically strong or innovative? Which theorists and critics were influential? The questions addressed here are meant to instigate a debate on the future of general and comparative literary theory in the Low countries. The issue consists of two parts: ‘The Text and its Limits’ focuses on intra-textual models and criticism, ‘Limits in Context’ looks at the impact and shape of trends and schools of literary studies in the Low Countries.